2021
DOI: 10.1016/j.lana.2021.100017
|View full text |Cite
|
Sign up to set email alerts
|

National and subnational trends of birthweight in Peru: Pooled analysis of 2,927,761 births between 2012 and 2019 from the national birth registry

Abstract: Summary Background National and subnational characterization of birthweight profiles lacks in low- and middle-income countries, yet these are needed for monitoring the progress of national and global nutritional targets. We aimed to describe birthweight indicators at the national and subnational levels in Peru (2012-2019), and by selected correlates. Methods We studied mean birthweight (g), low birthweight (<2,500 g) and small for gestational age (according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The mean birth weight of the sample was 3.08 kg (SD = 0.43), slightly below the Peruvian national average of 3.2 kg (Carrillo‐Larco et al, 2021). Mean anthropometric measurements at 0, 6, and 12 months old are provided in Table 2.…”
Section: Resultsmentioning
confidence: 65%
“…The mean birth weight of the sample was 3.08 kg (SD = 0.43), slightly below the Peruvian national average of 3.2 kg (Carrillo‐Larco et al, 2021). Mean anthropometric measurements at 0, 6, and 12 months old are provided in Table 2.…”
Section: Resultsmentioning
confidence: 65%
“… 13 , 14 , 32 Thus, PT, SGA and LGA may further represent the driving pathways for vulnerability, guiding the prioritization of preventive interventions and clinical care. 1 , 15 However, even if a previous ecological research in Peru found the prevalence of newborns with LBW and SGA was 6.2% and 5.2%, respectively, 34 no earlier study had comprehensively examined all these novel vulnerable newborn phenotypes at the subnational level in Peru.…”
Section: Discussionmentioning
confidence: 99%